Evaluation of patient satisfaction and masticatory performance in mandible single implant-assisted overdenture - Swati Kashyap; Sanjeev Mittal; Navneet Sharma; Urvashi Sukhija; Mohit Kamra; Nitika Gupta (Tzu Chi Medical Journal)
Objectives: Many authors' have advocated a minimum of two implants to support a mandibular overdenture, but financial restraints specifically among the geriatric population in developing countries made this treatment plan economically difficult. Hence, this study was planned to assess the symphyseal (midline) single implant-assisted complete overdenture for patient satisfaction and masticatory performance. Materials and Methods: In this clinical study, 12 edentulous first-time denture wearers underwent placement of a single implant in the mandibular symphyseal region. After 1 week, new complete dentures were fabricated and delivered to the patients. Post 3 months, the denture was fixed with a nylon cap-ball attachment to the anchor implant. Patients were questioned about comparison in the level of satisfaction and complaint before loading the implant (control group) and after 1 week, 1 month, and 3 months. The implant-assisted overdenture was fabricated with the help of a questionnaire. Masticatory performance was calculated with the help of a bite force measuring device at the same time intervals. SPSS 17.0 statistical software was used to analyze the data. Results: It was found that single implant anchorage of the mandibular complete denture resulted in a significant increase (P < 0.05) in patient's subjective satisfaction and a decrease (P < 0.05) in complaints at the end of 3 months. There was a significant (P < 0.01) increase in bite force in implant overdenture after 3 months (5.459 kgf) as compared to that of the complete denture (3.406 kgf). Conclusion: Single implant-assisted overdenture can be an appropriate treatment modality to treat edentulousness in the geriatric population. It insinuates the remarkable improvement of prosthesis function and oral comfort with minor surgical procedures.